2023
DOI: 10.1161/circresaha.122.321153
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent Nuclear Co-Trafficking of ASPP1 and p53 Aggravates Cardiac Ischemia/Reperfusion Injury

Abstract: OBJECTIVE: ASPP1 (apoptosis stimulating of p53 protein 1) is critical in regulating cell apoptosis as a cofactor of p53 to promote its transcriptional activity in the nucleus. However, whether cytoplasmic ASPP1 affects p53 nuclear trafficking and its role in cardiac diseases remains unknown. This study aims to explore the mechanism by which ASPP1 modulates p53 nuclear trafficking and the subsequent contribution to cardiac ischemia/reperfusion (I/R) injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…In cardiac ischemia-reperfusion injury, ASPP1 promotes cardiomyocyte apoptosis and severely impairs cardiac function. Different from the pro-apoptotic effects of ASPP1 in cancer cells and cardiomyocytes 9,22 , we discovered an interesting ability of ASPP1 to promote cardiac broblast proliferation and facilitate the development of cardiac brosis in the present study. ASPP1 exerts pro-apoptotic effects by tra cking to the nucleus to activate p53 or p53 family members and selectively enhance the transcription of pro-apoptotic genes downstream of p53 22,23 .…”
Section: Aspp1 Enhanced Apoptosis By Promoting Bax Expression As Well...mentioning
confidence: 53%
See 3 more Smart Citations
“…In cardiac ischemia-reperfusion injury, ASPP1 promotes cardiomyocyte apoptosis and severely impairs cardiac function. Different from the pro-apoptotic effects of ASPP1 in cancer cells and cardiomyocytes 9,22 , we discovered an interesting ability of ASPP1 to promote cardiac broblast proliferation and facilitate the development of cardiac brosis in the present study. ASPP1 exerts pro-apoptotic effects by tra cking to the nucleus to activate p53 or p53 family members and selectively enhance the transcription of pro-apoptotic genes downstream of p53 22,23 .…”
Section: Aspp1 Enhanced Apoptosis By Promoting Bax Expression As Well...mentioning
confidence: 53%
“…Among them, ASPP1 and ASPP2 augment the proapoptotic function of p53 by activating p53mediated transcription of proapoptotic genes, whereas iASPP has the opposite effect 8 . In a recent work, we found that ASPP1 exacerbates myocardial dysfunction following ischemia-reperfusion injury by binding to p53 and promoting myocardial apoptosis 9 . Mechanistically, ASPP1 facilitates the nuclear translocation of p53 and enhances the transcription of pro-apoptotic genes.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Activated EGR1 can also promote apoptosis by transactivating the proapoptotic targets, such as Egr-1 itself. In an earlier study, the researchers identified a novel EGR1/ASPP inter-regulatory loop and determined the proapoptotic function of cytoplasmic ASPP by stabilizing EGR1 and inhibiting the autophagy promoter ATG5 (Autophagy protein 5) -ATG12/ATG16 ( 57 , 58 ). The Tp53 controls TP53 by increasing its DNA binding and transactivation capabilities on proapoptotic gene promoters.…”
Section: Egr-1 Is Involved In Cardiac Cell Deathmentioning
confidence: 99%